Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12916-016-0715-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell-based adoptive immunotherapy eradicates and drives differentiation of chemoresistant bladder cancer stem-like cells

Abstract: BackgroundHigh-grade non-muscle invasive bladder cancer (NMIBC) has a high risk of recurrence and progression to muscle-invasive forms, which seems to be largely related to the presence of tumorigenic stem-like cell populations that are refractory to conventional therapies. Here, we evaluated the therapeutic potential of Natural Killer (NK) cell-based adoptive immunotherapy against chemoresistant bladder cancer stem-like cells (CSCs) in a pre-clinical relevant model, using NK cells from healthy donors and NMIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“… 37 In a bladder cancer mouse model, intravesical NK cell administration shows a significant higher infiltration rate than systemic delivery. 33 Furthermore, investigators at the University of Minnesota have clearly demonstrated in a mouse model with the OC cell line MA148 that the i.p. delivery route of activated NK cells is superior to i.v.…”
Section: Discussionmentioning
confidence: 99%
“… 37 In a bladder cancer mouse model, intravesical NK cell administration shows a significant higher infiltration rate than systemic delivery. 33 Furthermore, investigators at the University of Minnesota have clearly demonstrated in a mouse model with the OC cell line MA148 that the i.p. delivery route of activated NK cells is superior to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether transcript level changes in NK cell-associated signaling increased infiltrating lymphocytes in EPZ011989-treated xenografts, we used CD56 also known as Neural Cell Adhesion Molecule 1 (NCAM1) and NCR1 (Natural Cytotoxicity triggering Receptor 1) as markers of NK cells [36]. CD56 staining was significantly higher in combination-treated xenografts compared with vehicle, cisplatin and EPZ011989-treated mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, radiotherapy, in addition to eliminating tumour bulk, has been shown to induce the upregulation of NK cell‐activating ligands on surviving CSCs, enhancing NK cells cytotoxicity and improving survival when NK cells are infused in the host . On the other hand, adoptive transfer of NK cells can eliminate the cancer stem cell compartment making the tumour more differentiated and sensitive to chemotherapeutic drugs …”
Section: Natural Killer Cells and Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%